New Record of the Small Hive Beetle, Aethina tumida, in Africanized Honey Bee Colonies in Costa Rica - Calderón, Rafael (2019)
The small hive beetle (SHB) Aethina tumida Murray (Insecta: Coleoptera: Nitidulidae) is a honey bee parasite native to sub-Saharan Africa (Hepburn & Radloff, 1998). It was first described by Murray in 1867. In 1996, SHBs were discovered outside of their native range in colonies of European subspecies of honey bees in the southeastern USA (Elzen et al., 1999). Adult SHBs maintenance and reproduction occur inside and outside of social bee colonies and pupation in the soil (Neumann, Pettis, & Schafer, 2016) and cause considerable economic damage to apiculture in the USA (Hood, 2004; Neumann & Elzen, 2004) and Australia (Spiewok et al., 2007). During the last years, the SHB has been found in Africanized honey bee colonies in several countries of North and South America. It was detected in Mexico in October 2007 (Del Valle Molina, 2007; Neumann & Ellis, 2008) and in Brazil 2016 (Toufailia et al., 2017).In Central America, it was detected in El Salvador in 2013 (Office International des Epizooties, 2013) and Nicaragua in March 2014 (Calderón, Ramírez, Ramírez, & Villagra, 2015).In Nicaragua, the SHB location was confirmed in honey bee colonies located in San Juan del Sur-Rivas (South of the country), close to the border with Costa Rica (about eight km), which increases the risk of invasion of this pest into beehives in this country.